2016
DOI: 10.1080/17436753.2016.1186856
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of SiC fibres after exposure at elevated temperature

Abstract: To understand the service behaviour of SiC fibres, the effects of ambient environment and temperature on the microstructure, mechanical property and oxidation behaviour of these fibres were investigated. The result shows that, the surface of SiC fibres becomes rough after exposure in air from 973 to 1573 K due to the formation of small SiO 2 particles, and a smooth SiO 2 film will be formed on the SiC fibre at 1773 K. In Ar atmosphere, SiC fibres will change into clusters of large SiC crystals after heat treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Since Yajima et al reported their pioneering work about preparing silicon carbide (SiC) fibre from polycarbosilane (PCS) via a sequence of spinning, curing and pyrolysis in the 1970s, the precursor-derived method has been a primary way to prepare continuous and dense SiC fibre [1]. Up to date, the preparation method has been mature and the third generation of SiC fibre with high tensile strength (2.6-3.2 GPa), high elastic modulus (380-420 GPa) and excellent heat resistance (over 1800°C) has been achieved [2,3]. Due to its excellent properties, SiC fibre as a ceramic reinforcement for ceramic matrix composites has been widely applied in harsh environment, such as aerospace, nuclear, industrial and automotive [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Since Yajima et al reported their pioneering work about preparing silicon carbide (SiC) fibre from polycarbosilane (PCS) via a sequence of spinning, curing and pyrolysis in the 1970s, the precursor-derived method has been a primary way to prepare continuous and dense SiC fibre [1]. Up to date, the preparation method has been mature and the third generation of SiC fibre with high tensile strength (2.6-3.2 GPa), high elastic modulus (380-420 GPa) and excellent heat resistance (over 1800°C) has been achieved [2,3]. Due to its excellent properties, SiC fibre as a ceramic reinforcement for ceramic matrix composites has been widely applied in harsh environment, such as aerospace, nuclear, industrial and automotive [4][5][6].…”
Section: Introductionmentioning
confidence: 99%